MicroRNA regulation of human choline kinase gene expression - Ling, Few Ling (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2019)
Choline kinase (CK) is the first enzyme in the CDP-choline pathway for biosynthesis of phosphatidylcholine. Increased activity of CK has been implicated in human carcinogenesis. MicroRNAs (miRNAs) are a large family of non-coding RNAs that regulate gene expression. Dysregulation of miRNA expression is common in many types of cancer and miRNA profiling has the potential applications for cancer diagnostic and prognostic. Despite the physiological and pathological importance of CK, the regulation of its expression by miRNAs has never been reported. We hypothesize that miRNAs regulate the expression of CK and affect cell cycle progression. This study aims to predict the miRNAs that bind CK mRNAs and determine the effect of the selected miRNAs on CK gene expression, cancer cell proliferation and morphology. MiRNAs binding was predicted by several online computer programs that utilize different algorithms. Potential miRNAs were selected for the synthesis of their mimics and transfected into cancer cell lines. The effect of the miRNAs on CK alpha mRNA and protein levels were determined by real-time PCR and Western detection. MTT assay was used to determine the effect of miRNAs on cancer cell viability. The effect of miRNAs on cell morphology was investigated by scanning electron microscopy. Bioinformatic predictions of miRNAs that potentially downregulate human cka gene expression have produced ten best miRNA candidates (out ofinitial 54 non-repeating miRNAs) based on the higher scores for minimum free energy for interaction, binding site features and sequence conservation among different species. Due to the relatively large number of potential miRNA candidates, this study has focused on miRNAs targeting cka only although prediction for miRNAs targeting ckfl isoform was also conducted. Out of the ten shortlisted miRNAs potentially targeting cka, three miRNAs namely miR-876-Sp, miR-646 and miR-202-Sp were selected for experimental validation based on their favorable complementarity with cka gene 3'-untranslated region and binding energy.